2020
DOI: 10.11591/ijeecs.v20.i1.pp537-544
|View full text |Cite
|
Sign up to set email alerts
|

Optimal short-term hydro-thermal scheduling using multi-function global particle swarm optimization

Abstract: <p>An optimal short-term hydro-thermal scheduling (ST-HTS) problem is solved in this paper using the multi-function global particle swarm optimization (MF-GPSO). A multi-reservoir cascaded hydro-electric system with a non-linear relationship between water discharge rate, power generation and net head is considered in this paper. The ST-HTS problem determines the optimal power generation of hydro and thermal generators which is aimed to minimize total fuel cost of thermal power plants during a determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Salkuti et al [16] proposed multi-function global particle swarm optimization (MFGPSO) for optimal shortterm hydro-thermal scheduling (ST-HTS). This ideal ST-HTS optimizes hydro and thermal generator generating schedules to lower thermal power plant fuel costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salkuti et al [16] proposed multi-function global particle swarm optimization (MFGPSO) for optimal shortterm hydro-thermal scheduling (ST-HTS). This ideal ST-HTS optimizes hydro and thermal generator generating schedules to lower thermal power plant fuel costs.…”
Section: Introductionmentioning
confidence: 99%
“…From aforementioned literature, it is found that computation capacity and execution time is increased in [16], [17] breaks equality requirements while changing the violated dependent variables, [18] slows multimodal optimization convergence, in [19] swarm does not coalesce to a single spot, [21] cannot determine optimal scheduling, [22] does not address the objective function properly, in [23] algorithm is highly complex, [24] ignores social and cognitive factors for the PSO technique while [25] takes more computational time. The Hamilton and Egarch algorithm is a computational approach for optimizing the control of water flow in hydraulic systems based on certain criteria and constraints [26][27].…”
Section: Introductionmentioning
confidence: 99%